Answer:
T=-13
Explanation:
Simplifying
5t + 12 = 4t + -1
Reorder the terms:
12 + 5t = 4t + -1
Reorder the terms:
12 + 5t = -1 + 4t
Solving
12 + 5t = -1 + 4t
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Add '-4t' to each side of the equation.
12 + 5t + -4t = -1 + 4t + -4t
Combine like terms: 5t + -4t = 1t
12 + 1t = -1 + 4t + -4t
Combine like terms: 4t + -4t = 0
12 + 1t = -1 + 0
12 + 1t = -1
Add '-12' to each side of the equation.
12 + -12 + 1t = -1 + -12
Combine like terms: 12 + -12 = 0
0 + 1t = -1 + -12
1t = -1 + -12
Combine like terms: -1 + -12 = -13
1t = -13
Divide each side by '1'.
t = -13
Simplifying
t = -13